Jakarta’s Generation Z and Local Fashion Industry: Unveiling the Impact of Brand Image, Perceived Quality, and Country of Origin - Pantri Heriyati; Aryo Bismo; Monica Erwinta (Bina Nusantara University, 2024)
The local fashion industry in Indonesia faces tough competition with imported brands, driven by shifting consumer preferences, particularly during the pandemic. The research examined the impact of country of origin on purchase intention in the casual fashion industry, with brand image and perceived quality as intervening factors. It involved 412 Indonesian Gen Z in Jakarta as respondents with prior experience in the local casual fashion market. Data were collected through online questionnaires, and the SEM-PLS analysis method with SmartPLS v3.2.9 software was used for analysis. Results show that country of origin significantly influences brand image and perceived quality, affecting purchase intention. The research aligns with prior consumer perceptions studies. The implications offer guidance for casual fashion industry marketers and retailers. Emphasizing a positive country of origin image and focusing on brand image and perceived quality can impact purchase decisions, particularly among Indonesian Gen Z consumers in Jakarta. Future research can also expand the scope to include a broader sample and employ qualitative methods for deeper consumer insights. In conclusion, the research enhances understanding of consumer behavior in the casual fashion industry by revealing the role of country of origin, brand image, and perceived quality in shaping purchase intentions. Businesses can utilize these insights to refine their marketing strategies and better cater to their target consumers’ preferences.